The motif as a formula of imaginative poetic experience of the reality: A. N. Veselovsky’s methodology in contemporary Shakespeare studies. - Zelezinskaya, Natalia S. (Journal of the Belarusian State University. Philology, 2020)
The article postulates the need for a synthetic approach to the methodology of studying the motives of W. Shakespeare’s work as an author, whose work, on the one hand, is significantly removed from us in time, space and mentality, and on the other hand, the author absorbed the ideas of time and expressed them in the most aesthetically valuable form, in comparison with which other works of the era are traditionally evaluated. Hence we see the need to combine motif analysis, comparative analysis and the method of the history of ideas, which can be observed in the articles and notes of A. N. Veselovsky, which served as the theoretical basis of the study. In the works of the scientist, the motive is considered as the simplest narrative unit, a repeating unit and part of the literary tradition, and an artistic embodiment of a certain cultural idea. Particular attention is paid to the history of ideas (ideals – in Veselovsky’s terminology). Contemporary literary criticism (in particular, Shakespearean studies) is experiencing a surge of interest in the history of ideas and the synthesis of methods. The article demonstrates that this perspective has already been set by A. N. Veselovsky’s works and has deep roots. The return of attention to «Historical poetics» in the form in which it was conceived by scientists reveals its methodological and theoretical relevance for the modern stage of development of humanitarian knowledge. The methodology described in the article can be successfully applied in the study of specific literary motives, which was tested, in particular, on the motive of suicide in the works of W. Shakespeare.
Keywords: motif; motif analysis; comparative analysis; the history of ideas; context; A. N. Veselovsky; W. Shakespeare